Basalt fiber surface modifier for thermosetting resin composite material

By designing a triblock polymer coupling agent, the problem of difficulty in surface modification of basalt fibers is solved by using its chemical reactivity on basalt fibers and thermosetting resins, and the bonding strength and toughness of the composite material are significantly improved.

CN119823315AActive Publication Date: 2025-04-15SICHUAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510033210.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The surface of the basalt fibers is smooth and chemically inert, resulting in poor binding force with the thermosetting resin, affecting the overall performance of the composite material.

Method used

A triblock polymer coupling agent is designed to include olefins containing epoxy, aldehyde, carboxyl or amine groups, olefins containing no active functional groups and olefins containing silane groups, and react with basalt fibers and thermosetting resins through chemical bonds to enhance bond strength and toughness.

Benefits of technology

It effectively enhances the bonding strength between thermosetting resin and basalt fibers, while ensuring the toughness of the composite material and improving the overall performance of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823315A_ABST
    Figure CN119823315A_ABST
Patent Text Reader

Abstract

The invention discloses a basalt fiber surface modifier for a thermosetting resin composite material, and relates to the technical field of surface modifiers. The invention provides a structural general formula of the basalt fiber surface modifier and a preparation method of the basalt fiber surface modifier, and the basalt fiber surface modifier is used for modifying basalt fibers and preparing a thermosetting resin / basalt fiber composite material. The triblock polymer coupling agent with different functional groups is designed, the bonding strength of the thermosetting resin and the basalt fiber can be effectively enhanced, meanwhile, certain toughness is guaranteed, and the triblock polymer coupling agent is used for preparing the high-performance thermosetting resin / basalt fiber composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface modifiers, and in particular to a basalt fiber surface modifier for thermosetting resin composite materials. Background Art

[0002] With the development of science and technology, people have higher and higher demands for mechanical properties, specific strength and specific stiffness of materials, so composite materials came into being. Materials with comprehensive performance better than the performance of each component material are called composite materials by combining two or more materials with different forms and properties by chemical or physical methods. As a new type of material, composite materials have become an important pillar of high-performance structural materials, and together with polymer materials, inorganic non-metallic materials and metal materials, they are collectively called "four major materials". Among them, thermosetting resin-based composite materials (Thermoset Polymer Composites, referred to as "TSPC") have the advantages of light weight, high strength, corrosion resistance, fatigue resistance, good molding process, strong designability, etc., and are widely used in aerospace, sports and leisure, wind turbine blades, transportation, bridge construction and other fields. Thermosetting resin is a type of monomer molecule that undergoes a series of addition and condensation reactions under the action of curing agent, heat or radiation to form a three-dimensional cross-linked network, which is a basically irreversible cross-linked structure. It mainly includes epoxy resin, unsaturated polyester, phenolic resin, etc. After curing, thermosetting resins usually have problems such as high brittleness and insufficient toughness due to high crosslinking density, which has become a major obstacle in their application. Thermosetting resin-based composites are prepared by adding reinforcing materials to the resin matrix to form composites, which can significantly improve their strength, toughness, heat resistance, etc. At present, fiber materials such as carbon fiber, basalt fiber, glass fiber, and aramid fiber have been widely used as reinforcements for resin-based composites. Carbon fiber reinforced composites have the best mechanical properties, but their application in some fields is limited due to their high prices. Glass fiber reinforced composites are one of the most widely studied materials. Because of their low price and mechanical properties maintained at a certain level, they can be used as an affordable substitute for carbon fiber reinforced composites in certain specific occasions. The mechanical properties of basalt fiber reinforced composites are similar to those of glass fiber reinforced composites, and they are green and environmentally friendly and widely available. Therefore, cost-effective basalt fiber thermosetting resin-based composites have broad market prospects.

[0003] Basalt fiber is made of basalt ore as the main raw material, which is melted and drawn through a platinum plate. However, the surface of basalt fiber is smooth and chemically inert, with poor bundling and wettability, and poor adsorption capacity with most polymers. The interface bonding affects the compressive strength, impact strength, damage initiation threshold, fracture toughness, interlaminar shear, fatigue life, thermal properties and electrical properties of the composite material. There are obvious differences in physical properties between basalt fiber and resin matrix, which has a great influence on the uniform transmission of stress at the interface of the composite material. Therefore, in order to further improve the overall performance of basalt fiber reinforced resin-based composite materials, it is necessary to modify the basalt surface. By regulating the interface structure of thermosetting resin / basalt fiber, enhancing the interface bonding force, improving the load transfer capacity on the interface, and toughening the thermosetting resin matrix, the overall performance of the thermosetting resin / basalt fiber composite material can be enhanced.

[0004] As for inorganic / organic interface modification, the use of coupling agents can significantly improve the interface bonding strength. Silane coupling agent, as a commonly used modifier, is a compound composed of two groups with different chemical properties (organic group Y and hydrolyzed group X (OR)) connected to the same silicon atom. The schematic diagram of the surface mechanism of silane coupling agent modified materials is shown in Figure 1 As shown. The silane coupling agent is hydrolyzed to form silanol, which is further condensed to form hydrogen bonds or AO-Si (A represents the material matrix) bonds with the chemical groups on the surface of the material, so that the silane coupling agent is grafted and adsorbed on the surface of the material. As an important chemical reagent with a special structure that connects the surface of organic materials and inorganic materials, the silane coupling agent can react chemically with organic polymer materials to form carbon functional groups, and can also react chemically with the surface of inorganic polymer materials to form silicon functional groups. Therefore, whether it is organic or inorganic substances, different materials can be coupled together through the chemical or physical action of the silane coupling agent, further promoting the research and development of organic polymer composite materials and obtaining polymer materials with better performance.

[0005] The use of silane coupling agents in composite materials can significantly improve their mechanical properties, weather resistance, water resistance, flame retardancy, adhesion, dispersibility, formability and process operability. For the resin matrix, when using a silane coupling agent that is physically entangled with the resin matrix, the non-polar molecular chain of the small molecule coupling agent is short, and the physical bonding force is weak, which affects the comprehensive performance of the composite material. The use of polymer coupling agents can enhance the physical entanglement between the resin matrix and the interaction between the resin matrix and the inorganic filler, thereby optimizing the interface of the composite material. For thermosetting resin matrix, the use of small molecule silane coupling agents that can be chemically bonded with thermosetting resin can effectively increase the bonding strength between the resin and the inorganic filler. However, due to the short molecular chain of the small molecule, the bonding between the resin and the inorganic filler is too tight, resulting in the stress at the interface not being well released, which is not conducive to improving the toughness of the composite material. In contrast, polymer coupling agents can ensure effective bonding of the resin matrix and the inorganic filler, and form a flexible layer at the interface, relieve stress concentration, relax thermal stress, and achieve the purpose of toughening. At the same time, by changing the molecular weight and molecular structure of the polymer coupling agent, the strength and modulus of the coupling agent can also be adjusted, thereby achieving control and optimization of the interface structure between the filler and the matrix.

[0006] Although polymer coupling agents have more advantages than small molecule coupling agents, the current research on silane coupling agents is still mainly based on small molecule coupling agents, and the research on the synthesis of polymer silane coupling agents and their modification of composite materials is very lacking. In particular, there are few reports on the research of polymer silane coupling agents used in thermosetting resin / basalt fiber composites. The research on the directional design and synthesis of silane coupling agents for the surface modification of basalt fibers in thermosetting resin composites will help to further improve the comprehensive performance of thermosetting resin / basalt fiber composites and meet people's demand for higher performance composite materials. Summary of the invention

[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a basalt fiber surface modifier for thermosetting resin composite materials, design a triblock polymer coupling agent with different functional groups, which can effectively enhance the bonding strength between thermosetting resin and basalt fiber while ensuring a certain toughness, and is used to prepare high-performance thermosetting resin / basalt fiber composite materials.

[0008] The technical solution of the present invention to solve the above technical problems is as follows: a basalt fiber surface modifier for thermosetting resin composite materials is provided, and its general structural formula is:

[0009] -[Group A] x -[Group B] y -[Group C] z -;

[0010] Wherein, Group A is an olefin containing an epoxy group, an aldehyde group, a carboxyl group or an amine group;

[0011] Group B is olefins without active functional groups;

[0012] Group C is an olefin containing a silane group, a hydroxyl group, a carboxyl group, an isocyanate group, a phosphate group or a sulfonic acid group.

[0013] At the same time, since the surface modifier is a ternary random copolymer, the specific values ​​of x, y, and z cannot be determined.

[0014] Furthermore, x, y, z = 1:1:1.

[0015] Furthermore, Group B is ethylene, propylene or tetrafluoroethylene.

[0016] Furthermore, the basalt fiber surface modifier used for thermosetting resin composite materials has the structural formula:

[0017]

[0018] The present invention also provides a method for preparing the above-mentioned basalt fiber surface modifier for thermosetting resin composite materials, comprising the following steps:

[0019] (1) Compound 1, Compound 2 and Compound 3 were dissolved in toluene, and then dibenzoyl peroxide was added. The mixture was reacted at 80°C for 2 h under an argon atmosphere. Dibenzoyl peroxide dissolved in toluene was continued to be added, and the mixture was reacted at 80°C for 3 h. The mixture was cooled to room temperature, and then dropped into methanol for precipitation. The mixture was filtered to obtain a crude product.

[0020] (2) The crude product is dissolved in acetone, dropped into methanol for recrystallization, filtered, and vacuum dried to obtain a basalt fiber surface modifier for thermosetting resin composite materials.

[0021] Further, in step (1), the compound has a structural formula of

[0022] Further, in step (1), the structural formula of compound II is

[0023] Further, in step (1), the compound has the structural formula

[0024] Furthermore, in step (1), the molar volume ratio of compound 1, compound 2, compound 3 and toluene is 28.14 mmol: 28.14 mmol: 14.07 mmol: 40 mL.

[0025] Furthermore, the concentration of dibenzoyl peroxide was 1 wt %.

[0026] The present invention also provides application of the basalt fiber surface modifier for thermosetting resin composite materials in basalt fiber modification.

[0027] The present invention also provides the use of the basalt fiber surface modifier for thermosetting resin composite materials in the preparation of thermosetting resin / basalt fiber composite materials.

[0028] The present invention has the following beneficial effects:

[0029] 1. In order to enable the polymer to chemically bond with the thermosetting resin and basalt fiber at the same time, the olefin block polymer of the present invention requires at least three different olefin polymerization monomers, which are marked as: Group A, Group B, and Group C; wherein Group A contains a functional group that can chemically bond with the thermosetting resin, which is used to anchor the polymer itself on the resin matrix; Group C contains a functional group that can chemically bond with the basalt fiber, which is used to anchor the basalt fiber reinforcement; Group B does not chemically react with the thermosetting resin or the basalt fiber, and is mainly used to adjust the flexibility of the bonding between the resin matrix and the basalt fiber. Based on the above design, epoxy or imidazole groups are introduced into the Group A unit, which can chemically react with the active methylene hydroxyl group in the thermosetting resin such as phenolic resin and the epoxy group in the epoxy resin, and the stability of the chemical bond will affect its bonding strength. The silane group of the Group C unit undergoes a hydrolysis polymerization reaction on the surface of the basalt fiber when heated, thereby firmly bonding to the surface of the basalt fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the surface mechanism of materials modified by silane coupling agent;

[0031] Figure 2 is the infrared spectrum curve diagram of the product obtained in Example 1;

[0032] Figure 3 is the infrared spectrum curve diagram of the product obtained in Example 2;

[0033] Figure 4 This is the thermogravimetric curve of the product obtained in Example 1-2. DETAILED DESCRIPTION

[0034] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0035] Example 1

[0036] A basalt fiber surface modifier for thermosetting resin composite materials, the structural formula of which is:

[0037]

[0038] The preparation method of the basalt fiber surface modifier for thermosetting resin composite materials comprises the following steps:

[0039] (1) Compound 1 (4.00 g, 28.14 mmol), Compound 2 (2.93 g, 28.14 mmol) and Compound 3 (3.49 g, 14.07 mmol) were dissolved in toluene (40 mL), and then dibenzoyl peroxide (0.10 g, 1 wt%) was added. The mixture was reacted at 80° C. for 2 h under an argon atmosphere. Dibenzoyl peroxide (0.10 g, 1 wt%) dissolved in toluene was added continuously, and the mixture was reacted at 80° C. for 3 h. The mixture was cooled to room temperature, and the mixture was added dropwise into methanol for precipitation. The mixture was filtered to obtain a crude product.

[0040] (2) The crude product is dissolved in acetone, dropped into methanol for recrystallization, filtered, and vacuum dried to obtain a basalt fiber surface modifier for thermosetting resin composite materials.

[0041] Among them, the structural formula of compound 1 is The structural formula of compound II is The three structural formulas of the compound are

[0042] Example 2

[0043] A basalt fiber surface modifier for thermosetting resin composite materials, the structural formula of which is:

[0044]

[0045] The preparation method of the basalt fiber surface modifier for thermosetting resin composite materials comprises the following steps:

[0046] (1) Compound 1 (3.20 g, 28.14 mmol), Compound 2 (2.93 g, 28.14 mmol) and Compound 3 (3.49 g, 14.07 mmol) were dissolved in toluene (40 mL), and then dibenzoyl peroxide (0.10 g, 1 wt%) was added. The mixture was reacted at 80° C. for 2 h under an argon atmosphere. Dibenzoyl peroxide (0.10 g, 1 wt%) dissolved in toluene was added continuously, and the mixture was reacted at 80° C. for 3 h. The mixture was cooled to room temperature, and the mixture was added dropwise into methanol for precipitation. The mixture was filtered to obtain a crude product.

[0047] (2) The crude product is dissolved in acetone, dropped into methanol for recrystallization, filtered, and vacuum dried to obtain a basalt fiber surface modifier for thermosetting resin composite materials.

[0048] Among them, the structural formula of compound 1 is The structural formula of compound II is The three structural formulas of the compound are Test example

[0049] 1. The molecular structure of the product obtained in Example 1-2 was determined using a Spectrum Two Fourier infrared spectrometer. Potassium bromide was used to prepare the sample. The product to be tested and potassium bromide were dried in a vacuum drying oven before testing. The test results were as follows: Figure 2-3 shown.

[0050] Depend on Figure 2 It can be seen that the product obtained in Example 1 has a peak at 3026 cm -1 is the stretching vibration absorption peak of CH on the benzene ring, 1600cm -1 、1492cm -1 、1451cm -1 The absorption peak of the C=C chain in-plane stretching vibration on the benzene ring is 1730cm -1 It is the characteristic peak of the C=O double bond in the ester group; 1089cm -1 The characteristic peak of Si-O is at 1764cm -1 and 1850cm -1 The positions are the absorption peaks of symmetric and antisymmetric stretching vibration of CO bond in propylene oxide. It can be seen that the three units of Group A, Group B and Group C exist in the product TPCA-E obtained in Example 1.

[0051] Depend on Figure 3 It can be seen that the product obtained in Example 2 has a peak at 3026 cm -1 is the stretching vibration absorption peak of CH on the benzene ring, 1600cm -1 、1492cm -1 、1451cm -1The peak at 1730 is the characteristic peak of the C=C double bond in the ester group; the peak at 1089 is the characteristic peak of Si-O; at 1602cm -1 It is the stretching vibration absorption peak of the C=N bond. It can be seen that the three units of Group A, Group B and Group C exist in the product TPCA-N obtained in Example 2.

[0052] 2. The thermal stability of the product obtained in Example 1-2 was analyzed and tested using a NETZSCH TG209F1 thermogravimetric analyzer, with nitrogen as the protective atmosphere and a heating rate of 10°C / min. The results are as follows: Figure 4 shown.

[0053] Depend on Figure 4 It can be seen that the temperatures at which the basalt fiber surface modifiers TPCA-E and TPCA-N for thermosetting resin composite materials of the present invention lose 5% weight are 295° C. and 196° C., respectively, and at 320° C., the weight losses of TPCA-E and TPCA-N are both less than 10%. The above results show that both TPCA-E and TPCA-N have good thermal stability and meet the temperature requirements for basalt fiber surface modification.

[0054] 3. Prepare the material obtained in Example 1-2 as follows:

[0055] The basalt fiber and the polymer coupling agent TPCA-E or TPCA-N are dissolved in toluene, refluxed and stirred at 110°C for 5 hours, cooled to room temperature, and the liquid is added dropwise into methanol to precipitate a white solid. The solvent is removed by suction filtration, and the solid is dried under reduced pressure at 90°C to obtain a block-like white solid. Epoxy resin (10wt%), polyurethane (10wt%), aluminum hydroxide (10wt%) and sodium stearate (10wt%) are added into a kneader, stirred at room temperature for 30 minutes, and the modified chopped basalt fiber (60wt%) is added, stirred at room temperature for 10 minutes, and the mixed composite material is taken out.

[0056] The three-point bending method was used to measure the interlaminar shear strength of the composite material. The test standard adopted in the test was JC / T 773-2010, and the cutting size of the sample was thickness d = 2 ± 0.2 mm, length L = 20 mm, width b = 10 ± 0.5 mm, and span l = 5d.

[0057] The results are shown in Table 1.

[0058] Table 1 Effect of the amount of basalt fiber surface modifier added on the properties of composite materials

[0059]

[0060] It can be seen from Table 1 that the addition of the basalt fiber surface modifier for thermosetting resin composite materials of the present invention can effectively improve the shear strength of the composite materials. When the addition amount of TPCA-E is 15%, the composite material finally obtained has the optimal interlaminar shear strength performance.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A basalt fiber surface modifier for thermosetting resin composite materials, characterized in that: Its general structural formula is: -[Group A] x -[Group B] y -[Group C] z -; Wherein, Group A is an olefin containing an epoxy group, an aldehyde group, a carboxyl group or an amine group; Group B is olefins without active functional groups; Group C is an olefin containing a silane group, a hydroxyl group, a carboxyl group, an isocyanate group, a phosphate group or a sulfonic acid group.

2. The basalt fiber surface modifier for thermosetting resin composite materials according to claim 1, characterized in that: Group B is ethylene, propylene or tetrafluoroethylene.

3. The basalt fiber surface modifier for thermosetting resin composite materials according to claim 1, characterized in that: Its structural formula is:

4. The method for preparing the basalt fiber surface modifier for thermosetting resin composite materials according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Compound 1, Compound 2 and Compound 3 were dissolved in toluene, and then dibenzoyl peroxide was added. The mixture was reacted at 80°C for 2 h under an argon atmosphere. Dibenzoyl peroxide dissolved in toluene was continued to be added, and the mixture was reacted at 80°C for 3 h. The mixture was cooled to room temperature, and then dropped into methanol for precipitation. The mixture was filtered to obtain a crude product. (2) The crude product is dissolved in acetone, dropped into methanol for recrystallization, filtered, and vacuum dried to obtain a basalt fiber surface modifier for thermosetting resin composite materials.

5. The method for preparing a basalt fiber surface modifier for thermosetting resin composite materials according to claim 4, characterized in that: In step (1), a compound having a structural formula is 6. The method for preparing a basalt fiber surface modifier for thermosetting resin composite materials according to claim 4, characterized in that: In step (1), the structural formula of compound II is 7. The method for preparing a basalt fiber surface modifier for thermosetting resin composite materials according to claim 4, characterized in that: In step (1), the compound has the structural formula 8. The method for preparing a basalt fiber surface modifier for thermosetting resin composite materials according to claim 4, characterized in that: In step (1), the molar volume ratio of compound 1, compound 2, compound 3 and toluene is 28.14 mmol: 28.14 mmol: 14.07 mmol: 40 mL.

9. Use of the basalt fiber surface modifier for thermosetting resin composite materials according to any one of claims 1 to 3 in basalt fiber modification.

10. Use of the basalt fiber surface modifier for thermosetting resin composite materials according to any one of claims 1 to 3 in the preparation of thermosetting resin / basalt fiber composite materials.

Citation Information

Patent Citations

  • Method for preparing toughened unsaturated polyester glass fibre composite material

    CN101531763A

  • Cellulose fiber-reinforced resin molded article and method for producing same

    CN115702191A

  • Basalt fiber reinforced vinyl ester resin composite material and preparation method thereof

    CN116063822A

  • Modified acrylic resin, preparation method thereof, powder coating and application

    CN117402286A

  • Polyphenylene sulfide composite material for capacitor shell and preparation method of polyphenylene sulfide composite material

    CN119081406A